Implementasi Sistem Hidroponik Deep-Flow-Technique (DFT) untuk Pemanfaatan Pekarangan di Desa Mekar Jaya - Badu, Risti Ristianingsih; Ijonu, Ukhti Nurfajriah Sasmita; Lukum, Wahidin; Paputungan, Nursiti Aisyah; Ajami, Frans Mitran; Abas, Mamat; Podungge, Abdul Madjid; Sahabat, Andi Inar; Juramang, Risnayanti R.; Umadji, Nur Inda R.; Radjak, Karmila Damariani (Jurnal Suara Pengabdian 45, 2025)
The utilization of home yard as an alternative food source by using innovation has not been well applied in Melandar Meiland village. Household food security is usually not managed planned. To achieve sustainable use of the yard, this devotion aims to implement the Deep Flow Technique (DFT) hydroponic system. Moreover, the method used in this activity is participation through the observation of initial conditions, socialization and education through extension and discussion, the application of hydroponic installation, and planting maintenance of plants. The results of the activity show that people better understand the benefits of yard and the ability to run the DFT hydroponic system independently. Thus, the application of this system encourages changes in the views and habits of society about the yard as a productive place to support household food security.